2009
DOI: 10.1177/1352458508096871
|View full text |Cite
|
Sign up to set email alerts
|

Increase of CD4+TNFα+IL-2−T cells in cerebrospinal fluid of multiple sclerosis patients

Abstract: Intracellular production of TNFalpha and IL-2 after stimulation with phorbol myristate/ionomycin was flowcytometrically measured in CD4(+) T cells from peripheral blood (PB) and cerebrospinal fluid (CSF) of 29 patients with multiple sclerosis (MS), and 16 with other inflammatory and 41 with other non-inflammatory neurological diseases. In CSF, the percentages of CD4(+)TNFalpha(+)IL-2(-)T cells were significantly higher in patients with MS than either of the controls, whereas no difference was found in CD4(+)TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…Enumeration of the captured cells showed increased frequency of both CD4+ and CD8+ T cells (Table 1). Our observation again agrees with previous findings showing increases of CD4+ T cells in CSF of inflammatory diseases in the CNS 71,72 . Increases of CD4+ T cells in CSF, which can assume a helper–I T cell phenotype and secrete pro-inflammatory cytokines, may indicate brain inflammation and related neuronal damage 73 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Enumeration of the captured cells showed increased frequency of both CD4+ and CD8+ T cells (Table 1). Our observation again agrees with previous findings showing increases of CD4+ T cells in CSF of inflammatory diseases in the CNS 71,72 . Increases of CD4+ T cells in CSF, which can assume a helper–I T cell phenotype and secrete pro-inflammatory cytokines, may indicate brain inflammation and related neuronal damage 73 .…”
Section: Resultssupporting
confidence: 93%
“…Our preliminary study showed that the total trafficking leukocyte counts in AD patients’ CSF modestly increased compared to normal CSF leukocyte counts. An increased frequency of both CD4+ and CD8+ T cells was observed, which agrees with previous findings that there are elevations of both T cell subsets in the brain of neurodegenerative disease 71,72 . AD patients exhibited significantly altered profiles of leukocyte phenotypes, confirming the recent notion that the increased migration of CD8+ cytotoxic T cells is associated with AD development.…”
Section: Discussionsupporting
confidence: 92%
“…Inflammatory processes within the CNS involve activated microglia, astrocytes, macrophages and lymphocytes releasing a plethora of anti-and pro-inflammatory cytokines including both IFN-gamma and TNF-alpha [43]. This occurs in a number of inflammatory neurodegenerative disorders, including multiple sclerosis, in which high levels of TNF-alpha within cerebrospinal fluid and infiltration of IFN-gamma secreting activated T-cells into the brain is seen [44][45][46]. Neuroinflammation and subsequent microglial activation plays an important role in the pathogenesis of several neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 97%
“…Production of TNF-␣ by bone marrow T cells has been linked to bone loss associated with estrogen deficiency (36,37). In addition, the presence of TNF-␣-producing T cells correlates with disease severity and progression in multiple sclerosis (38,39). Finally, the production of TNF-␣ by alloreactive T cells was shown to predict allograft rejection (40).…”
Section: Discussionmentioning
confidence: 99%